Knowledge, Attitudes, and Risk Perception Toward Avian Influenza Virus Exposure Among Cuban Hunters - Delgado-Hernández, Beatriz; Mugica, Lourdes; Acosta, Martin; Pérez, Frank; Montano, Damarys de las Nieves; Abreu, Yandy; Ayala, Joel; Percedo, María Irian; Alfonso, Pastor (Frontiers in Public Health, 2021)
The first step for decreasing zoonotic disease threats is a good understanding of why and where are the risks. Hunters, are among those people frequently dealing with potentially infected birds, so they may be the more exposed to avian influenza viruses (AIVs). The objective of the current study was to gain a better understanding of Cuban hunters’ general harvesting practices, knowledge and risk perception on avian influenza. An anonymous and voluntary semi-structured questionnaire was designed and applied to 398 hunters. Multiple correspondence analyses found relationships with potential exposure of AIVs to people and domestic animals. The main associated risks were flu unvaccinated (60.1%) and don’t cleaning the hunting knives (26.3%); direct contact with water (32.1%) and clean wild birds at home (33.2%); receive assistance during bird cleaning (41.9%), to have poultry at home (56,5%) and feeding domestic animals with wild bird leftovers (30.3%). The lack of some protective measures reported by hunters had no relationship with their awareness on avian influenza, which may imply insufficiency of such knowledge. The results evidenced that more effective risk communication strategies about the consequences of AIVs infecting human or other animals, and the importance of reducing such risk are urgent needs.